Gender-related differences in the effects of Inonotus obliquus polysaccharide on intestinal microorganisms in SD rats model - Hu, Binhong; He, Xinyue; Tan, Jin; Ma, Yichuan; Wang, Gang; Liu, Songqing; Li, Mingyue; Guo, Yanping; Sun, Rong; Sun, Mengxue; Deng, Xin; Zhou, WenJing; et al. (Frontiers in Veterinary Science, 2022)
Natural edible fungal polysaccharides are of research and application value for the prevention of diseases by improving the microenvironment within the intestine. Inonotus obliquus polysaccharide (IOP) extracts have strong antioxidant, anti-inflammatory, and other biological activities, and as such, it could be used as prebiotics to improve the viability of intestinal microbes, maintain intestinal homeostasis and improve intestinal immunity. The effects of sex on intestinal microbiota after IOP absorption was determined. In this study, IOP had different effects on the intestinal flora of male and female rats, with the diversity and richness showing opposite changes. At the same time, after IOP intervention, changes in the dominant intestinal flora of female rats were less compared with that of males. In addition, while Clostridia, Lactobacillus and Roseburia were the dominant intestinal microbes in female rats, males had mainly Bacteroidota from different families and genera, along with an increasing proportion of Muribaculaceae from different families and genera. IOP could further regulate the intestinal microenvironment of male and female SD rats by enhancing the vitality of their dominant microorganisms, and for both sexes, this enabled the screening of dominant microflora that were conducive to the balance of the intestinal flora. These results help to understand the effects of sex-related differences on the composition of the intestinal microbiota as well as on diseases.